ANALISIS MODEL KEGAGALAN RUMAH 2 LANTAI AKIBAT NEGATIVE SKIN FRICTION DAN CURAH HUJAN YANG TINGGI - Jeanfrie Chandra; Chaidir Anwar Makarim (JMTS: Jurnal Mitra Teknik Sipil, 2021)
ABSTRACTOne of the problems that appear in a project is the presence of soft soil. In projects with soft soil types, it is necessary to manage the soil to increase the bearing capacity of soil. Soil subsidence on soft soil causes friction between the soil and the pile blanket, called the negative skin friction. Negative skin friction should not be neglected because it exerts a large enough force on the load that the pile must support. In addition, in designing an engineer must also pay attention to the optimal rainfall that will occur during the construction of a project and after that has an impact on the quality of the soil and foundation used. The topography of a project also needs to be considered, building a house on the edge of a slope can cause problems with slope instability. Increasing the load on the edge of the slope can reduce the safety factor of a slope. In this study, a modeling analysis will be carried out on a 2-story residential building that causes the house to collapse due to failure of the foundation design, the existence of negative frictional resistance on soft soil, and slope stability. ABSTRAKSalah satu permasalahan yang muncul pada suatu proyek adalah adanya tanah lunak. Pada proyek dengan jenis tanah lunak, perlu dilakukan perbaikan tanah untuk meningkatkan daya dukung tanah. Penurunan tanah pada tanah lunak menyebabkan gesekan antara tanah denan selimut tiang yang disebut fenomena tahanan friksi negatif. Tahanan friksi negatif tidak boleh diabaikan karena memberikan gaya yang cukup besar terhadap beban yang harus ditopang oleh tiang. Oleh karena itu, seorang insinyur harus memperhatikan dan mengetahui mengenai perilaku tanah lunak. Selain itu dalam mendesain, seorang insinyur juga harus memperhatikan mengenai curah hujan optimal yang akan terjadi selama pengerjaan suatu proyek dan setelahnya yang berdampak pada kualitas tanah dan fondasi yang digunakan. Topografi suatu proyek juga perlu diperhatikan, membangun rumah di tepi lereng dapat menyebabkan permasalahan pada ketidakstabilan lereng.